Study on evolution law of coal permeability characteristics under long-term stress - Zhenping SUN (Meikuang Anquan)
In the process of gas extraction, deep coal is affected by high ground stress for a long time. In order to explore the permeability characteristics and evolution law of coal under long-term stress. A coal permeability model considering the interaction between creep and matrix-fracture under long-term stress is established. The internal expansion coefficient is defined to reflect the contribution of matrix expansion deformation caused by gas adsorption to the change of total volume and fracture volume, and it is introduced into the classical stress-strain constitutive equation. The experimental data based on fractional derivative transient pulse method is used to estimate the permeability and verify the accuracy of the permeability model. The results show that the permeability decreases gradually during the first and the second stages of creep caused by long-term stress, which is consistent with the physical process in which the initial cracks and pores are gradually compacted. In addition, compared with the existing classical models, the proposed permeability model shows better performance in describing the evolution trend of permeability. Parameter analysis shows that under constant effective volumetric strain, small internal expansion coefficient makes effective volumetric strain play a dominant role in permeability evolution, while large internal expansion coefficient leads to adsorption expansion strain increment playing a dominant role in permeability evolution of deep coal seam.